Karakteristik Pedagang Pasar Kuliner Di Taman Kota Singaraja - I Gusti Made Dharma Hartawan (ARTHA SATYA DHARMA, 2020)
Based on the results of research obtained from several informants about the characteristics of traders in the Singaraja City Park culinary market which is based on indicators of individual characteristics according to Robbins (2006) which includes: 1) age, where age is not an obstacle for traders to do business but it is used as motivation for them to work hard to achieve their desires in life. 2) gender, where in building a business you do not know how a person's gender is, but if there is a strong will within yourself and want to work hard, whatever is expected can be achieved. 3) trust, regarding the trader's trust in doing a business, must be confident, believe in God Almighty, work hard and always believe in yourself. 4) The level of education, by having education not only increases one's knowledge in doing a business, but will also make a trader who has a professional character in dealing with any conditions experienced as well as facing competition with other traders.